Transformational Leadership Behavior and Organizational Commitment of Meranaw Deans and Teachers in Teacher Education Institutions - Sultan, Rohanie M. (Journal of Social Sciences (COES&RJ-JSS), 2017)
Educational institutions in Mindanao play a vital role in the crafting of good governance and effective leadership. Ever since education is a powerful force in moulding the character and values of future leaders to become productive citizens of the nation and blaze the path to enduring peace and unity, and progress. With this, the researcher was driven to investigate whether transformational leadership behaviors and organizational commitment are evident among the deans and teachers in Teachers Education Institutions in Lanao del Sur, Philippines. Descriptive- correlational survey method was employed in the study. There were 23 Meranaw deans and 189 teachers who participated in the study. Modified Multifactor Leadership Questionnaire and Organizational Commitment Questionnaire were the instruments used. The data gathered were analyzed and interpreted. The findings revealed that both the deans and the teachershave moderately high level of organizational commitment. Based on the deans’ self-rating, there is significant relationship between the following elements: (1) affective commitment to intellectual stimulation and individualized consideration; (2) continuance commitment to intellectual stimulation; and (3) normative commitment to idealized influence and inspirational motivation. However, on the teachers’ rating regarding the deans’ transformational leadership shows a significant relationship between their transformational leadership behavior and teachers’ organizational commitment. This concludes that the leadership behavior of deans can positively influence the organizational commitment of teachers.